Communities, psychotherapeutic innovation and the diversity of international qualitative research in mental health. Issue 4 (1st October 2016) - Harper, David
Abstract: The articles in this special issue are hugely varied in terms of their country of origin (Brazil, Finland, Italy, Malaysia and the UK); theoretical influences (e.g. Lacanian theory, cultural-historical approaches and relational theories) and method of qualitative analysis (e.g. content and thematic analyses, Lacanian discourse analysis, Grounded theory, ethnography and auto-ethnography). In this commentary, I will discuss each article in turn before moving on to address some common issues including: the relationship between therapeutic innovation and research; differing implicit models of subjectivity; the need for theoretically pluralistic approaches to interpretation; and the need to incorporate the views of service users.